Adaptation of transient well test results - Dmitrii A. Martyushev; Inna N. Ponomareva; Weijun Shen (Записки Горного института, 2023)
Transient well tests are a tool for monitoring oil recovery processes. Research technologies implemented in pumping wells provide for a preliminary conversion of measured parameters to bottomhole pressure, which leads to errors in determining the filtration parameters. An adaptive interpretation of the results of well tests performed in pumping wells is proposed. Based on the original method of mathematical processing of a large volume of field data for the geological and geophysical conditions of developed pays in oil field, multidimensional models of well flow rates were constructed including the filtration parameters determined during the interpretation of tests. It is proposed to consider the maximum convergence of the flow rate calculated using a multidimensional model and the value obtained during well testing as a sign of reliability of the filtration parameter. It is proposed to use the analysis of the developed multidimensional models to assess the filtration conditions and determine the individual characteristics of oil flow to wells within the pays. For the Bashkirian-Serpukhovian and the Tournaisian-Famennian carbonate deposits, the influence of bottomhole pressure on the well flow rates has been established, which confirms the well-known assumption about possible deformations of carbonate reservoirs in the bottomhole areas and is a sign of physicality of the developed multidimensional models. The advantage of the proposed approach is a possibility of using it to adapt the results of any research technology and interpretation method.